(untitled) (Architecture Image Studies, 2025)
Clear+Park (C+P) use 3D laser scanning to create works that operate across architecture, installation, and media arts. C+P capture, edit and manipulate point-cloud data to document spaces, create speculative projects and spatial propositions; creating digital images and animations that engage with and respond to specific site narratives. In their work, C+P create complex assemblages that combine 3D rendering and post-production effects to create spatial collages that operate between the actual and the virtual. Using the veracity and verisimilitude of the scans opens a powerful opportunity to critique traditional forms of representation where conceptions of authenticity and specificity of place can be radically questioned. In the same way, the images of architectural photography do not simply reflect the inherent qualities of the architecture but actively construct those qualities. Author Biographies Nic Clear, Professor of Architecture & Dean of School of Arts and Humanities, University of Huddersfield Professor Nic Clear is a qualified architect, writer and curator. He is Professor of Architecture and Dean of the School of Arts and Humanities at the University of Huddersfield. He was a Professor of Architecture and Head of the Department of Architecture and Landscape at the University of Greenwich, having previously taught at the Bartlett School of Architecture for over 20 years. In 2015, he was the Inaugural Professor for Research in Visionary Cities at the Institute of Fine Arts in Vienna, and has taught in the UK, Europe, the US and Canada. Hyun Jun Park, Course Director Postgraduate Architecture, Leeds Beckett University Hyun Jun Park is a practitioner, writer, curator, fellow of the Royal Society of Arts and Course Director for Postgraduate Architecture at the Leeds School of Architecture, Leeds Beckett University. Prior to this, he was Course Leader for the Master of Architecture at the University of Huddersfield and taught postgraduate M.Arch design studio at the University of Greenwich. Before he came to the UK, he was an associate architect at SAMOO Architects & Engineers (SAMSUNG Corp), Seoul, Korea. He was awarded M.Arch by the Bartlett School of Architecture and finished his BA and first master’s degree at Hongik University, Seoul, Korea. Clear + Park Clear+Park use 3D laser scanning to create multidisciplinary works that operate across architecture, installation, and media arts. Clear+Park use 3D scanning to capture spaces and create spatial representations and narratives that engage with, and respond to specific site histories and spatial practices. Through their research Clear+Park explore ways in which architects and artists can reproduce, develop, manipulate, and represent spaces using advanced digital technology in ways that engage with non-specialist audiences.